(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Physical inactivity remains a pressing public health issue in Europe, with a disproportionate impact on populations facing health inequalities. Health creation – defined as enabling the conditions for individuals to achieve physical, mental, and social wellbeing – calls for innovative and inclusive measurement tools. This study introduces the Health Creation Index (HCI), a novel composite measure capturing modifiable individual, social, and environmental contributors to wellbeing. To demonstrate the utility of the HCI, we applied it to evaluate the impact of Beat the Street (BTS), a gamified, community-wide walking and active travel programme. Pre- and post-intervention data were analysed for 22,350 BTS participants, of whom 73% were female, 16% lived in the most deprived areas (IMD 1–2), 6% were aged 60+, and 19% reported long-term health conditions. Matched post-intervention data were available for 5,885 individuals. At baseline, 54% of participants met the Active Lives Survey criteria for physical activity. After the intervention, 13% had moved from inactive to active status. HCI scores improved by 2.5% among these newly active individuals, compared to a 1.5% average increase across all participants. Lower HCI scores were recorded among people with disabilities (3.49/5), and higher scores among women (3.75/5). Participants who were active at baseline consistently showed higher HCI scores than their inactive counterparts (p < 0.01). These findings highlight the potential of walking-based community interventions to enhance protective factors for health creation and reduce wellbeing disparities. The HCI offers a practical framework to identify those most in need and to guide inclusive, place-based strategies in physical activity promotion.